Perbedaan Pengaruh Faktor Makroekonomi Terhadap Return Saham Perusahaan Consumer Goods Dan Real Estate - Agung Wibowo (Media Ekonomi dan Manajemen, 2013)
AbstractInvestments in the securities markets can be classified as high-risk investments, because of the nature of the commodity is very sensitive to changes in the macroeconomic sector, including inflation, interest rates, and exchange rate rupiah / U.S. Dollar. This study aimed to examine differences in the effect of inflation, interest rate, and exchange rate Rupiah / U.S. Dollar on stock return consumer goods companies and stock return real estate company. This study were used a sample 29 consumer goods companies and 30 real estate companies that listed on the Indonesia Stock Exchange over the period 2007 to 2011. The sample taken using purposive sampling, and the analysis tools used were Chow test with dummy variable method. The study found that there is a significant negative effect of inflation and the interest rate on stock return consumer goods companies and stock return real estate companies, as well as a significant positive effect of exchange rate of Rupiah / U.S. Dollar on stock return consumer goods companies and stock return real estate companies. The study also found that the effect of the interest rate to the stock return real estate companies greater than the effect of interest rate on stock return consumer goods companies, but there is no difference in the effect of inflation and exchange rate of Rupiah / U.S. Dollar on stock return consumer goods companies and stock return real estate companies. Keywords : Inflation, Interest Rate, Exchange Rate Rupiah / U.S. Dollar, Consumer Goods, and Real Estate